Morbidity and early outcome of transurethral resection of prostate: A prospective single-institute evaluation of 100 patients - Shrestha, B; Baidya, JL (Kathmandu University Medical Journal, 2010)
Background: Transurethral resection of the prostate underwent significant technical improvements during the last decades, with major impact on the incidence of intra and postoperative complications. Objectives: The objective of the study was to analyse the early complications and to predict immediate outcomes of transurethral resection of prostate (TURP) in a single tertiary care institute. Materials and methods: We prospectively evaluated 100 patients undergoing transurethral resection of prostate at B and B Hospital, Gwarko, Lalitpur, Nepal, from August 2008 till April 2009. Case records containing 32 variables concerning preoperative status, operative details, complications and immediate outcome were recorded for each patient. Results: The cumulative short-term postoperative significant morbidity was 10% and the peroperative morbidity was 6%. The most relevant postoperative complication was failure to void (24%). Among significant postoperative morbidities, surgical revision had to be performed in two patients (2%), open prostatectomy in one patient, transurethral resection (TUR) syndrome in 5% and significant urinary tract infection in 2%. Among significant intra operative morbidity, we had one case with bladder perforation, significant cardiac arrhythmia requiring prompt attention in 4% and TUR syndrome during resection in 1%. We did not have any mortality related to the procedure during the study period. The resected tissue averaged 25.67gm. Incidental carcinoma of the prostate was diagnosed by histological examination in 4% of patients. Urine peak flow rate (Q-max) increased to 12.88ml per second from 9.24ml per second and average fl ow rate increased to 7.36 ml per second from 5.03 ml per second. The postoperative mean residual urine measured by ultrasound decreased to 28.46ml from preoperative 86.59 ml. Conclusions: TURP has, for decades, been the standard surgical therapy for lower urinary tract symptoms secondary to benign prostatic hyperplasia though significant morbidities can be associated with the procedure. Meticulous preoperative workup and proper selection of the patients for the procedure significantly improve the outcome after transurethral resection of the prostate. Key words: TURP ( Transurethral resection of prostate); LUTS ( Lower urinary tract symptoms); BOO (Bladder outlet obstruction) DOI: 10.3126/kumj.v8i2.3559 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 203-207